Lithographically Defined Zerogap Strain Sensors - Moghaddam, Mahsa Haddadi; Dalayoan, Daryll J.C.; Park, Daehwan; Wang, Zhihao; Kim, Hwanhee; Im, Sunghoon; Ji, Kyungbin; Kang, Daeshik; Das, Bamadev; Kim, Dai Sik (ACS Photonics, 2024)
Metal thin films on soft polymers provide a unique opportunity for resistance-based strain sensors. A mechanical mismatch between the conductive film and the flexible substrate causes cracks to open and close, changing the electrical resistance as a function of strain. However, the very randomness of the formation, shape, length, orientation, and distance between adjacent cracks limits the sensing range as well as repeatability. Herein, we present a breakthrough: the Zerogap strain sensor (ZSS), whereby lithography eliminates the randomness and violent tearing process inherent in conventional crack sensors and allows for short periodicity between gaps with gentle sidewall contacts, critical in high strain sensing enabling operation over an unprecedentedly wide range. Our sensor achieves a gauge factor of over 15,000 at an external strain of ϵext = 18%, the highest known value. With the uniform gaps of four-to-ten thousand nanometer widths characterized by periodicity and strain, this approach has far reaching implications for future strain sensors whose range is limited only by that of the flexible substrate, with non-violent operations that always remain below the tensile limit of the metal.
Keywords: Adjacent cracks; Crack sensors; Electrical resistances; Flexible substrate; Gage factors; Mechanical; Metal thin film; Soft polymers; Strain sensors; Zerogap; crack sensors; gauge factor; metal thin film; strain sensors; Zerogap